Belief in omens and superstitions among patients with chronic neurological disorders - Rūta Mameniškienė; Rasa Kizlaitienė; Rūta Kaladytė Lokominienė; Kristijonas Puteikis (Frontiers Media S.A., 2024)
IntroductionChronic neurological disorders may affect various cognitive processes, including religiosity or superstitious belief. We investigated whether superstitious beliefs are equally prevalent in patients with Parkinson's disease (PD), people with epilepsy (PWE), patients with multiple sclerosis (MS) and healthy controls (HCs).MethodsFrom late 2014 to early 2023 we conducted a cross-sectional in-person anonymous paper-based survey at the tertiary clinic of Vilnius University Hospital Santaros Klinikos among outpatients and HCs by asking them to ascribe meaning or report belief for 27 culturally adapted statements (9 omens and 18 superstitions). The sum of items that a respondent believes in was labeled the superstition index (SI). The SI was compared between groups by means of the Kruskal-Wallis (H) test and negative binomial regression modeling. A two-step cluster analysis was performed to discern different subgroups based on answers to the items of the SI.ResultsThere were 553 respondents who completed the questionnaire (183 PWE, 124 patients with PD, 133 with MS and 113 HCs). Complete SI scores were collected for 479 (86.6%) participants and they were lower in patients with PD (n = 96, Md = 1, IQR = 0-5.75) in comparison to those with epilepsy (n = 155, Md = 6, IQR = 1-14), MS (n = 120, Md = 4, IQR = 0-12) or HCs (n = 108, Md = 4.5, IQR = 1-10), H (3) = 26.780, p < 0.001. In a negative binomial regression model (n = 394, likelihood ratio χ2 = 35.178, p < 0.001), adjusted for sex, place of residence, income and education, female sex was the only characteristic associated with the SI (β = 0.423, OR = 1.526, 95% CI = 1.148 to 2.028). Both female sex (β = 0.422, OR = 1.525, 95% CI = 1.148 to 2.026) and Parkinson's disease (β = −0.428, OR = 0.652, 95% CI = 0.432 to 0.984) were significant predictors of the SI when age was removed from the model. Two-step cluster analysis resulted in individuals with PD being grouped into "extreme non-believer," "non-believer" and "believer" rather than "non-believer" and "believer" clusters characteristic for PWE, patients with MS and HCs.ConclusionOur study suggests that individuals with PD believe in less superstitions than patients with MS, PWE or HCs. The results of this investigation should be independently confirmed after adjusting for PD-specific variables.